Exergetic and Economic Evaluation of CO2 Liquefaction Processes - Feng Chen; Tatiana Morosuk (Energies, 2021)
The transport of CO2, as a part of the carbon capture and storage chain, has received increased attention in the last decade. This paper aims to evaluate the most promising CO2 liquefaction processes that can be used for port-to-port and port–offshore CO2 ship transportation. The energetic, exergetic, and economic analyses are applied. The liquefaction pressure has been set to 15 bar (liquefaction temperature −30 °C), which corresponds to the design of the existing CO2 carriers. The three-stage vapor-compression process has been selected among closed systems (with propane-R290, ammonia-R717, and R134a as the working fluid) and the precooled Linde–Hampson process—as the open system (with R717). The three-stage vapor-compression process R290 shows the lowest energy consumption, and the CO2 liquefaction cost 21.3 USD/tCO2. Although the power consumption of precooled Linde–Hampson process is 3.1% higher than the vapor-compression process with R209, the lowest total capital expenditures are notable. The CO2 liquefaction cost of precooled Linde–Hampson process is 21.13 USD/tCO2. The exergetic efficiency of the three-stage vapor-compression process with R290 is 66.6%, while the precooled Linde–Hampson process is 64.8%.